Estudo da correlação entre motivação, estilo de aprendizagem e os tipos psicológicos Junguiano - Toledo, Evelyn Jeniffer de Lima (2015)
The motivation, learning style and the student's personality are constructs that have been studied in the field of educational psychology and is considered extremely important in teaching and learning processes. However, there is little research on this subject especially in quantitative terms. It is this gap that this research is inserted in order to answer the following research questions "There is a correlation between motivation, learning style and personality? and if so, how is it?" To answer this question we used 6 questionnaires: EMA, MSLQ-A, Psychological Types, LSI, ILS, MSLQ-B. Only the LSI proved inappropriate because of its low internal consistency. As results were found correlations ranging from weak to strong depending on the constructs in question, being more intense when constructs aimed at measuring different perspectives of the same factor, which shows a good consistency between the questionnaires. In addition, correlations were found between intrinsic motivational factors and academic performance and between "anxiety" and motivational extrinsic factors. Anxiety was also correlated with the learning style called "training" and therefore it is suggested that teachers do not encourage such style mainly students with anxiety problems. Furthermore, positive correlations were found between intrinsic and extrinsic factors indicating the presence of a not exclude the other, they can coexist. Intrinsic motivation was correlated with the psychological type via the perception factor, being positive and moderate to "intuition" and is also correlated to the learning style through the construct "critical thinking", indicating that it is favored intuitive individuals. "Critical thinking" also correlated favorably directly or indirectly, in the format of "metacognitive self-regulation", "time and study environment" and "regulation effort". Moreover, the positive correlation between these factors indicates that the development of a strategy for development is siding other. Therefore, it is concluded that there are correlations between the constructs and they suggest how to nourish or discourage certain styles.